New dictionary of Christian ethics and pastoral theology - Atkinson, David John, 1943-; Field, David H. (Leicester, UK IVP, 1995)
Includes bibliographical references.
Keywords: Christian ethics -- dictionaries; Pastoral theology -- dictionaries